Implementasi Kebijakan Pembangunan Jalan Antar Kecamatan Di Kabupaten Kediri - Sekarsari, Retno Wulan; Suyeno, Suyeno (JU-ke: Jurnal Ketahanan Pangan, 2018)
Implementation of Inter-Sub-Regency Road Development Policy in the Regency of Kediri (A Study on the Public Construction Office of Kediri Regency). This research is conducted based on the numerous criticisms addressed to the road development policy that has been implemented in the Kediri Regency. All this time, the road development policy in the Regency of Kediri has been considered discriminative towards the rural community. The Bina Marga Public Construction Office as the implementer of road development policy, under the authority of the Regency, has been putting higher priority on the road developments from the Regency capital to the sub-regency capitals, inter-sub-regency capital, and from the sub-regency capitals to villages. Meanwhile, the rural road developments (inter-village connecting roads and in-village roads) tend to be put aside. As a result, the rural community must develop the roads independently. The higher the self-supporting level in developing the roads is, the lower the allocation of financial aids for road development from the Regency Government of Kediri given to those villages will be.Â Keyword: Road Development Policy; Policy Implementation